Effect of LiCl concentration in the polymer dope on the structure and performance of hydrophobic PVDF hollow fiber membranes for CO2 absorption - Mansourizadeh, Amir (Elsevier, 2010)
Effect of lithium chloride (LiCl) concentration as non-solvent additive in the spinning dopes on the structure and CO2 absorption performance of the polyvinylidene fluoride (PVDF) membranes was investigated. The hollow fiber membranes were prepared via a wet phase-inversion process and characterized in terms of gas permeability, wetting resistance, mass transfer resistance and overall porosity. The morphology study indicated that by increasing LiCl concentration in the spinning dope, the membrane structure changed from the finger-like to the sponge-like. In addition, by increasing LiCl concentration up to 4wt.% a drastic decrease in the N2 permeance and a significant increase in the wetting resistance were observed. CO2 absorption by distilled water was conducted through the gas-liquid membrane contactors. Using LiCl in the spinning dopes, the CO2 flux of the prepared membranes significantly improved. By introducing 2wt.% LiCl, the PVDF membrane showed a CO2 flux of approximately 60% higher than the plain PVDF membrane at the absorbent flow rate of 200ml/min. It can be concluded that a porous hydrophobic hollow fiber membrane with improved structure can be a productive alternative for CO2 absorption and separation through gas-liquid membrane contactors.